Academic writing errors: An analysis of English research papers of Thu Dau Mot University Journal of Science - Nguyen, Thi Man (2020)
Không đồng ý về việc phục vụ đọc trực tuyến, không đồng ý về việc cho chép file và cho photo 50% tài liệu; References: p.62 - 66; 5 chapters: Introduction; Literature review; Methodology; Findings And Discussion; Conclusion; Master thesis of Thu Dau Mot University. Major: English language; Code: 8220201